Integrated business solution: e-Supplier / Kow Huey Ping - Kow , Huey Ping (2002)
The growth of the Internet and other powerful technological infrastructures allowing companies of all shapes and sizes to add value to the traditional business process, both internally and externally. The project, Integrated Business Solution (IBS), is designed to integrate all the main backend and front-end system of a company, as well as with third party such as banking institute and the supplier. This is important in streamlining the business transaction and critical data flow among the trading communities. e-supplier is one of the modules in this IBS project. It is designed to facilitate the business process between the buyer and the supplier. This system provides three modules to meet different needs from general user, registered customer and the administrator. All users are allowed to view the catalogue and place order online. Personalization page function is deployed in this system for the registered customers to allow them to do order tracking and furthermore, reorder easily. Value added to both parties. In the administrator module, one of the important features in this system is the ability to create an electronic link and sharing operational information with the customer/ buyer inventory system to improve supply chain, and increase speed and flexibility. Inventory and sales data are retrieved from the customer's backend system for value-added supply chain. Electronic catalogue was implement to aid the business process and eliminate the traditional paper-based catalogue and paper-form; this will make the business transaction more cost-effective. The system is developed using Web-based approach, which enable the users to reach on the system remotely regardless of the time and location. ASP technology was deployed to enhance the dynamic content and improve interactive functionality. Besides, Windows 2000 Server, ITS, Microsoft SQL Server 7.0, HTML, and VBScript are implemented in this project. Microsoft Visual InterDev is used as Web development tool.